Okonomischer Nutzen der überlappenden Einleitung: Untersuchung mithilfe eines Computersimulationsmodells. - Hunziker S; Baumgart A; Denz C; Schüpfer G; Hunziker, S; Baumgart, A; Denz, C; Schüpfer, G (Der Anaesthesist, 2009)
The aim of this study was to investigate the potential economic benefit of overlapping anaesthesia induction given that all patient diagnosis-related groups (AP DRG) are used as the model for hospital reimbursement. A computer simulation model was used for this purpose. Due to the resource-intensive production process, the operating room (OR) environment is the most expensive part of the supply chain for surgical disciplines. The economical benefit of a parallel production process (additional personnel, adaptation of the process) as compared to a conventional serial layout was assessed. A computer-based simulation method was used with commercially available simulation software. Assumptions for revenues were made by reimbursement based on AP DRG. Based on a system analysis a model for the computer simulation was designed on a step-by-step abstraction process. In the model two operating rooms were used for parallel processing and two operating rooms for a serial production process. Six different types of surgical procedures based on historical case durations were investigated. The contribution margin was calculated based on the increased revenues minus the cost for the additional anaesthesia personnel. Over a period of 5 weeks 41 additional surgical cases were operated under the assumption of duration of surgery of 89+/-4 min (mean+/-SD). The additional contribution margin was CHF 104,588. In the case of longer surgical procedures with 103+/-25 min duration (mean+/-SD), an increase of 36 cases was possible in the same time period and the contribution margin was increased by CHF 384,836. When surgical cases with a mean procedural time of 243+/-55 min were simulated, 15 additional cases were possible. Therefore, the additional contribution margin was CHF 321,278. Although costs increased in this simulation when a serial production process was changed to a parallel system layout due to more personnel, an increase of the contribution margin was possible, especially with procedures of shorter duration (<120 min). For longer surgical times, the additional costs for the workforce result in a reduced contribution margin depending on the models chosen to handle overtime of the technical OR personnel. Important advantages of this approach for simulation are the use of the historical production data and the reflection of the specificities of the local situation. Computer simulation is an ideal tool to support operation room management, particularly regarding the planning of resource allocation and the coordination of workflow.